Effect of Varied Packages of Combination Training on Self Concept of Men Basketball Players: The Impact of Varied Packages of Combination Training on the Self Concept of Men Basketball Players (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The present study was undertaken to analyze the effect of varied packages of combination training on self concept level of basketball players. Total N=48, inter collegiate level participated men basketball players chosen from National Institute of Technology, Tadepalligudem, Andhra Pradesh, India. Their age ranged from 18-25 years. The basket players chosen for the study were divided into four equal groups n=12 and designated as experimental group ‘A’ experimental group ‘B’ experimental group ‘C’ and control group ‘D’. combined weight - plyometric training [Package I]were given to group ‘A’ combined plyometric - speed training [Package II]were given to group ‘B’ combined basketball training with yoga practice treatment [Package III] were given to group ‘C’ and the ‘CG’ control group ‘D’ were restricted to participate in any activities. The trainings were given for a period of twelve weeks. The data were collected before and after the training on self concept through Questionnaire (Muktha Rani Rastogi). The obtained data’s were analyzed by Analysis of Covariance (ANCOVA). The level of significant was fixed at 0.05 levels. The results of the study showed that training Package I, II, III significantly increased self concept level the basketball players when comparative with control group. Thefore there is no significant differences found between three experimental groups’ basketball players.